Design of moldable hydrogels for biomedical applications using dynamic covalent boronic esters. (June 2019) - Marco-Dufort, B.; Tibbitt, M.W.
Abstract: Traditional polymeric materials based on thermosets or thermoplastics are applied broadly as biomedical materials. While attractive for a range of applications, thermosets and thermoplastics can be limited by their relatively static materials properties. Recent efforts in materials design has focused on engineering responsive and adaptive networks based on dynamic covalent chemistries. Installing reversible chemistries within the network backbone enables breaking and reforming of bonds in the network and associated rearrangement of the material on experimental timescales. The complexation between boronic acids and diols to form reversible boronic esters has emerged as a safe and synthetically tractable dynamic covalent cross-linking motif for the design of stimuli-responsive biomedical materials. Here, we present an instructive review on the design of dynamic covalent networks and gels using boronic ester cross-links. We provide a detailed discussion of boronic ester chemistry with guidelines for tuning the binding based on synthetic modification. We explain how network topology and connectivity influence the macroscale properties of the assembled networks. In addition, we discuss how these design principles have been used in foundational and emerging biomedical applications of boronic ester–based hydrogels. The use of boronic esters as dynamic covalent cross-links will continue to produce materials with emergent dynamic properties, and the design principles presented here will aid in the fabrication of next-generation boronic ester-based biomaterials. Graphical abstract: Image 1